COMMUNIST HERITAGE AS THE WELFARE STATE POINT OF REFERENCE. POLAND’S CASE STUDY (Studia Politica. Romanian Political Science Review, 2025)
This study explores the legacy of the communist welfare state in Poland and its impact on contemporary social democracy. It examines how Polish leftist parties have engaged with the socio-economic achievements of the Polish People’s Republic (PRL) whilenavigating post-communist political cleavages. Through historical and comparative analysis, the paper investigates how Polish social democracy has used its communist heritage in shaping its policy agenda, particularly regarding welfare provisions such as housing,education, and healthcare. The findings suggest that while the Polish left has at times strategically employed the achievements of the PRL in political discourse, recent shifts – marked by a retreat from this historical narrative – have weakened its electoral appeal.The study raises questions about whether Polish social democracy can leverage its historical legacy to advocate for a stronger welfare state in an era of neoliberal dominance.